Quality evaluation of Medicago sativa materials belonging to the Italian ecotype 'Romagnola' - Torricelli R.; Veronesi F.; Mazza L.; Schiatti F. (Quality in lucerne and medics for animal production, 2001)
On the basis of preliminary results concerning the analysis of lucerne variability for quality traits, it seems worthwhile paying more attention to the variability between entries than within: within entry variability seems quite difficult to handle, even if the absence of a negative correlation of statistical significance between dry matter yield and crude protein content deserve a certain interest. To this respect, a large number of single plants should be analysed to apply selection differentials within lucerne populations and to start with a breeding program. Such a breeding approach could be quite expensive and it is difficult to propose to private breeders in the absence of a clear economic return in terms of higher market prices for higher quality lucerne products.
14. Réunion Eucarpia du Groupe Medicago spp., 2001/09/12-15, Zaragoza and Lleida (Spain)